Hubungan Perilaku Makan dengan Body Dissatisfaction pada Mahasiswa Gizi Universitas Aisyah Pringsewu Tahun 2024 - Fauziyah Lathifatul Azhar; Dera Elva Junita; Desti Ambar Wati; Aftulesi Nurhayati (Journal on Education, 2024)
Individuals in the adolescent phase lack knowledge that poor eating behavior will affect nutritional status. A body that is less than ideal will result in body dissatisfaction in the form of restricting food consumption, improper eating behavior, and a strict diet that does not meet the needs of the body. Students are one of the areas affected by body dissatisfaction, students tend to care about body image which is also influenced by the environment. The purpose of this study is to analyze the relationship between eating behavior and body dissatisfaction in nutrition students of Aisyah Pringsewu University in 2024. This study used a cross sectional approach. The population in this study amounted to 263 students, while the sample of 93 students was taken using the purposive sampling method with inclusion criteria willing to fill in informed consent, regular students with active status, ≥20 years old, and able to communicate well. Body dissatisfaction data was measured by the BSQ 34 questionnaire, and eating behavior was measured by the EAT 26 questionnaire. Data collection was carried out on May 27 – June 14, 2024 in the S1 Nutrition Study Program. The data obtained was then analyzed by gamma test. The results of this study obtained the highest data of respondents with a positive body image of 58.5%, and good eating behavior of 80.9%. The results of the analysis of UIJ gamma data showed that there was no significant relationship between eating behavior and body dissatisfaction with p=0.751 (p <0.05).